Specification of energy assessment methodologies to satisfy ISO 50001 energy management standard. (October 2017) - Kanneganti, Harish; Gopalakrishnan, Bhaskaran; Crowe, Ed; Al-Shebeeb, Omar; Yelamanchi, Tarun; Nimbarte, Ashish; Currie, Kenneth; Abolhassani, Amir
Abstract: Energy management has become crucial for the industrial sector as a structured approach to lowering the cost of production and in reducing the carbon footprint. With the development of ISO 50001 standard, energy management has enticed the attention of upper level management in terms of continuous improvement. The ISO 50001 standard requires an intensive energy assessment process to identify SEUs and EnPI, based on which target energy reductions can be realized. Such an energy assessment approach can be easily developed based on the IAC energy assessment protocol and other approaches so as not to "re-invent" the wheel but instead focus and refine the process to generate knowledge and information that would assist manufacturers to initiate and determine the focus areas for energy reduction and develop the ensuing documentation. The aim of this work is to develop an energy assessment methodology and reporting format tailored to the needs of ISO 50001. The developed energy assessment methodology integrates the energy reduction aspect of an energy assessment with the requirements of Sections 4.4.3 (Energy Review) to 4.4.6 (Objectives, Targets and Action Plans) in ISO 50001, thus enabling facilities to reduce the time and other resources required for facilitating the implementation of ISO 50001.